1994
DOI: 10.1007/bf01627594
|View full text |Cite
|
Sign up to set email alerts
|

Le sinus sphénoïdal pendant l'enfance : aspects en IRM du developpement normal

Abstract: To obtain baseline standards of normal age-related development of the sphenoid sinus during childhood magnetic resonance images of the sphenoid sinus in 401 patients less than 15 years old were reviewed. T1-weighted sagittal and T2-weighted axial scans were evaluated for bone marrow conversion, development of pneumatization, spatial enlargement and septation of the sphenoid sinus. The sphenoid sinus had a uniformly low signal intensity (red bone marrow) on T1-weighted images in all children less than 4 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 16 publications
7
28
0
2
Order By: Relevance
“…In various literature studies, the incidence of a single septum has been reported as 33-95 percent. [11] With a few specific exemplary cases the incidence of a single septum was reported as 77% (Szolar et al) [12] and 71% (Hamid et al), [13] while we found single septum (single complete+single incomplete) in 90.7% of our cases. These studies indicated that septa were mostly in the paramedian location and more frequently deviated to the right side.…”
Section: Discussionsupporting
confidence: 42%
“…In various literature studies, the incidence of a single septum has been reported as 33-95 percent. [11] With a few specific exemplary cases the incidence of a single septum was reported as 77% (Szolar et al) [12] and 71% (Hamid et al), [13] while we found single septum (single complete+single incomplete) in 90.7% of our cases. These studies indicated that septa were mostly in the paramedian location and more frequently deviated to the right side.…”
Section: Discussionsupporting
confidence: 42%
“…In contrast, some anatomical and radiological studies demonstrated that sphenoid pneumatization begins during the first months of age and is usually completed within the first decade [22,23,24]. Detailed radiological assessment with computerized tomography and MRI is essential to investigate the anatomical variations of paranasal sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…Development of the skull base has been proven to be asynchronous and asymmetrical. 14,15 As growth of the midfacies accelerates in late childhood, 1 midsagittal craniocaudal expansion of the skull base also accelerates. However, we show that the dorsal portions have a more rapid development and reach maturation earlier, at 5-7 years, compared with the more anterior compartments of the cranial base.…”
Section: 19mentioning
confidence: 99%